Parental labour supply responses to the abolition of day care fees - Mathias Huebener; Astrid Pape; C. Katharina Spiess (Journal of Economic Behavior & Organization, 2020)
This paper provides evidence that low private contributions to highly subsidised day care constrain mothers from working longer hours. We study the effects of reforms that abolished day care fees in Germany on parental labour supply. The reforms removed private contributions to highly subsidised day care in the year before children enter primary school. We exploit the staggered reform across states with a difference-in-differences approach and event studies. Although participation in day care is almost universal for preschoolers, we provide evidence that the reforms increase the intensity of day care use and the working time of mothers by about 7.1 percent. Single mothers, mothers with no younger children, mothers in denser local labour markets, and highly educated mothers react most strongly. We find no evidence for labour supply responses at the extensive margin and no evidence of responses in paternal labour supply. The effects on maternal labour supply fade away by the end of primary school as mothers in the control group also gradually increase their labour supply as their children grow older.
Keywords: J13; J22; J38; 330; Labour supply; Childcare costs; Family policy; Event study